The Perfect Storm: Abnormal Baseline QT With Chronic Methadone Use and Serious Hypokalemia - Oscar J. Lopez MD; Diana Othon MD; Yilen K. Ng-Wong MD; Jose Sleiman MD (SAGE Publishing, 2024)
Methadone, a well-known drug used for pain control and as a treatment for opioid addiction, can cause arrhythmias, including torsades de pointes (TdP), which may progress to ventricular fibrillation and sudden death. We present a case of a middle-aged woman with a long history of methadone use who presented to the emergency department after experiencing cardiac arrest at home. During her hospitalization, she experienced multiple episodes of TdP that improved with isoproterenol and potassium correction. The initial diagnosis was methadone-induced prolonged QT. However, even with discontinuation of methadone, her QTc remained prolonged. Congenital long QT syndrome was suspected, and genetic testing was instructed to test in the outpatient setting. She was discharged on nadolol and a LifeVest.